2022
DOI: 10.3389/fvets.2022.902775
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study Investigating the Behavioural Development of Bitches in a Guide Dog Training Programme Neutered Prepubertally or Post-Pubertally

Abstract: There are few studies that investigate the effect of neutering bitches before or after puberty. The majority of current literature examining the impact of the timing of neutering on health and behaviour has used age rather than the onset of puberty as the key variable. The aim of this prospective cohort study was to investigate the effects of timing of neutering in relation to puberty on behaviour in female dogs reared and trained in an assistance dog programme. The study examined data for bitches neutered bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Retrospective studies investigating the effect of gonadectomy on behaviour are often confounded since important factors like age at gonadectomy, environmental factors and history of the individual dog are sometimes not considered, and a control group is frequently missing (Arlt et al, 2017). Confounding factors in questionnaire-based studies may be subjective interpretation of behaviour, lack of experience and ignorance of dog behaviour and body language (Moxon et al, 2022). This may contribute to the fact that some studies report no effect and others detrimental effects following gonadectomy (Kim et al, 2006;McGreevy et al, 2018;O'Farrell & Peachey, 1990;Spain et al, 2004aSpain et al, , 2004b.…”
Section: Behavioural Concernsmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective studies investigating the effect of gonadectomy on behaviour are often confounded since important factors like age at gonadectomy, environmental factors and history of the individual dog are sometimes not considered, and a control group is frequently missing (Arlt et al, 2017). Confounding factors in questionnaire-based studies may be subjective interpretation of behaviour, lack of experience and ignorance of dog behaviour and body language (Moxon et al, 2022). This may contribute to the fact that some studies report no effect and others detrimental effects following gonadectomy (Kim et al, 2006;McGreevy et al, 2018;O'Farrell & Peachey, 1990;Spain et al, 2004aSpain et al, , 2004b.…”
Section: Behavioural Concernsmentioning
confidence: 99%
“…The results of behavioural studies based on questionnaires are often difficult to evaluate as owners may be unable to distinguish between different types of aggression (Maarschalkerweerd et al., 1997). Further confounding factors may be subjective interpretation of behaviour, lack of experience and lack of knowledge of dog behaviour and body language (Moxon et al., 2022). Age at gonadectomy might be important in certain cases of aggressive behaviour, with earlier operation preventing an increase in learned unwanted behaviour that cannot be influenced by later gonadectomy or hormonal therapy (Heidenberger & Unshelm, 1990).…”
Section: Health Benefits Of Sterilisation With Loss Of Gonadal Steroi...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent cohort study showed that female Labradors and Golden Retrievers, neutered before puberty, were more likely to have aggression factor scores that increased between the 1st and 3rd year of life; however, only a small number of bitches displayed only mild aggressive behaviors. There was no impact of pre- or post-pubertal neutering on other behavioral factors [ 38 ].…”
Section: Reviewmentioning
confidence: 99%
“…For many years, surgical castration was the only reliable and permanent method of contraception in dogs. Ovariectomy, ovariohysterectomy (OHC) and orchidectomy are the most common surgical procedures routinely performed in small animal practice [1,2]. Prepubertal ovariectomy (or OHC) is defi ned as the surgical castration of immature female animals between 6 to 14 weeks of age, and it is often associated with some long-term behavior and health effects [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%